Inhibition of acrylamide formation in potato strip by ultrasonic-treated methylcellulose batter - Lua, Hwee Ying; Naim, Mohd Nazli; P. Mohammed, Mohd Afandi; Hamidon, Fariza; Abu Bakar, Noor Fitrah; Vangnai, Kanithaporn (John Wiley and Sons, 2022)
The ultrasonic (US)-treated batter mixtures of commercial methylcellulose (MC) as the fried potato strips' coating layer were demonstrated. The layer formed a rapid gel that absorbs the substrate's water content and related functional groups that contribute to acrylamide formation reduction. Different concentrations of MC (0.5-2.0 w/v %) mixtures were subjected to US at 20 W to evaluate coating layers' effect prior to the deep-frying process. At 1% w/v concentration batter mixture, the USMC layer reduced the highest acrylamide value. For comparison purposes, the differences in the acrylamide content of the USMC, the non-USMC and the uncoated samples were 64.7 ± 5.04, 156.4 ± 7.44 and 344.1 ± 5.39 ng g-1, respectively. The results were supported with lower oil uptake and water retention of the USMC compared with the non-USMC with the values of 2.2 g/100g and 28.6 g/100g with 5.1 g/100g and 47 g/100g, respectively.